Kualitas Layanan Publik di Kantor Investasi Layanan Terpadu Satu Pintu dan Tenaga Kerja (DPMPTSP & TK) di Kabupaten Bone Bolango - Djaafar, Lucyane (Gorontalo Journal of Government and Political Studies, 2018)
Public service is a part that cannot be separated from the life of the nation and state. The 1945 Constitution mandates that the state must provide good service to all citizens to fulfill their basic needs. The government is one of the providers of public services must always carry out services that are in accordance with the rules and must know the conditions of those served. In fact, the community is often disappointed with the services provided by the government in terms of licensing arrangements such as long and convoluted service procedures, the issuance of a permit is sometimes not in accordance with the time set. Problem formula What is the quality of public services in the One Stop and Manpower Integrated Services Investment Office (DPMPTSP & TK) in Bone Bolango Regency?                This research uses qualitative methods. Techniques for collecting data through observation, interviews, documentation. The results of the service quality of Bone Bolango District's One-Stop Integrated Service and Labor Service (DPMPTSP & TK) have been good, seen from the dimensions of tangibles, responsiveness dimensions, empathy (empathy) but on assurance (assurance) dimensions and reability dimensions. corrected because there is still a relationship with the relevant office in issuing a letter of recommendation so that the permit issuance is not in accordance with the stipulated time.